A 2-Dose AERAS-402 Regimen Boosts CD8+ Polyfunctionality in HIV-Negative, BCG-Vaccinated Recipients - Sivakumaran, Dhanasekaran; Blatner, Gretta; Bakken, Rasmus; Hokey, David; Ritz, Christian; Jenum, Synne; Grewal, Harleen M. S. (Frontiers in Immunology, 2021)
Despite the widespread use of BCG, tuberculosis (TB) remains a global threat. Existing vaccine candidates in clinical trials are designed to replace or boost BCG which does not provide satisfying long-term protection. AERAS-402 is a replication-deficient Ad35 vaccine encoding a fusion protein of the M. tuberculosis (Mtb) antigens 85A, 85B, and TB10.4. The present phase I trial assessed the safety and immunogenicity of AERAS-402 in participants living in India – a highly TB-endemic area. Healthy male participants aged 18–45 years with a negative QuantiFERON-TB Gold in-tube test (QFT) were recruited. Enrolled participants (n=12) were randomized 2:1 to receive two intramuscular injections of either AERAS-402 (3 x 1010 viral particles [vp]); (n=8) or placebo (n=4) on study days 0 and 28. Safety and immunogenicity parameters were evaluated for up to 182 days post the second injection. Immunogenicity was assessed by a flow cytometry-based intracellular cytokine staining (ICS) assay and transcriptional profiling. The latter was examined using dual-color-Reverse-Transcriptase-Multiplex-Ligation-dependent-Probe-Amplification (dc-RT MLPA) assay. AERAS-402 was well tolerated, and no vaccine-related serious adverse events were recorded. The vaccine-induced CD8+ T-cell responses were dominated by cells co-expressing IFN-γ, TNF-α, and IL-2 (“polyfunctional” cells) and were more robust than CD4+ T-cell responses. Five genes (CXCL10, GNLY, IFI35, IL1B, and PTPRCv2) were differentially expressed between the AERAS-402 group and the placebo group, suggesting vaccine-induced responses. Further, compared to pre-vaccination, three genes (CLEC7A, PTPRCv1, and TAGAP) were consistently up-regulated following two doses of vaccination in the AERAS-402-group. No safety concerns were observed for AERAS-402 in healthy Indian adult males. The vaccine-induced predominantly polyfunctional CD8+ T cells in response to Ag85B, humoral immunity, and altered gene expression profiles in peripheral blood mononuclear cells (PBMCs) indicative of activation of various immunologically relevant biological pathways.